Distinct New York City Aedes albopictus Mosquito Populations Display Differences in Salivary Gland Protein D7 Diversity and Chikungunya Virus Replication - Maria E. Kaczmarek; Nora L. Herzog; Maria G. Noval; John Zuzworsky; Zahir Shah; Waheed I. Bajwa; Kenneth A. Stapleford (Viruses, 2020)
In an increasingly interconnected world, the exposure and subsequent spread of emergent viruses has become inevitable. This is particularly true for Aedes (Ae.) mosquito-vectored viruses, whose range has increased over the past decade from tropical to temperate regions. However, it is unclear if all populations of Ae. mosquitoes in temperate New York City are able to successfully replicate and transmit arboviruses. To answer this question, we reared Ae. albopictus mosquitoes living in a temperate climate from three locations in New York City. We first sequenced the salivary antiviral protein D7 from individual mosquitoes in each population and found single nucleotide variants that are both shared and unique for each Ae. albopictus population. We then fed each population chikungunya virus (CHIKV) via an artificial blood meal. All three mosquito populations could be infected with CHIKV, yet viral titers differed between populations at 7 days post infection. Moreover, we found that these mosquitoes could transmit CHIKV to mice, and that virus RNA reached the saliva as early as two days post infection. Upon sequencing of the saliva CHIKV genomic RNA, we found mutations at sites correlated with increased transmission and virulence. These studies show that NYC Ae. albopictus populations can be infected with and transmit CHIKV, CHIKV is able to evolve in these mosquitoes, and that host salivary factors display population-specific diversity. Taken together, these studies highlight the need to study how distinct mosquito populations control viral infections, both at the virus and host level.